Fabrication and characterization of hydroxyapatite based biocompatible composite scaffold for bone tissue engineering - Das, Poulomi (BRAC University, 2018)
This dissertation is submitted in Partial Fulfillment of the Requirements’ for the Degree of Master of Science in Biotechnology 2017.